SENSORY RESPONSE OF WET NOODLES WITH SUBSTITUTION OF SUPER RED DRAGON FRUIT (Hylocereus costaricensis) PEEL - Yuliani Yuliani; Alberth Parlindungan; Marwati Marwati; Krishna Purnawan Candra (Agroindustrial Technology, University of Trunojoyo Madura, 2021)
Innovation in increasing the wet noodles performance was conducted by substituting super red dragon fruit (pitaya) peel (DFP) puree to get DFP wet noodles that have red color and rich in fiber. Wheat flour (WF) was substituted with super red DFP puree in a portion of 0-20%. A single factor experiment arranged in Completely Randomized Design with four replications for each treatment was conducted. Hedonic and quality hedonic properties for color, aroma, texture, and taste were determined. Data were analyzed by the Friedman test continued by the Wilcoxon Sign Rank test. The DFP wet noodle with DFP puree substitution of 10% gave the best hedonic sensory response for overall acceptability with the properties of like for color, texture, and taste, but rather like for aroma. The DFP wet noodles have hedonic quality properties of a light reddish color, slightly scented of dragon fruit peel with a texture of rather hard and rather taste of DFP. The fiber content of the DFP wet noodles was 0.135 ± 0.003%.